Audit mode change, corporate governance and audit effort - Limei Cao; Wanfu Li; Limin Zhang (China Journal of Accounting Research, 2015)
This study investigates changes in audit strategy in China following the introduction of risk-based auditing standards rather than an internal control-based audit mode. Specifically, we examine whether auditors are implementing the risk-based audit mode to evaluate corporate governance before distributing audit resources. The results show that under the internal control-based audit mode, the relationship between audit effort and corporate governance was weak. However, implementation of the risk-based mode required by the new auditing standards has significantly enhanced the relationship between audit effort and corporate governance. Since the change in audit mode, the Big Ten have demonstrated a significantly better grasp of governance risk and allocated their audit effort accordingly, relative to smaller firms. The empirical evidence indicates that auditors have adjusted their audit strategy to meet the regulations, risk-based auditing is being achieved to a degree, reasonable and effective corporate governance helps to optimize audit resource allocation, and smaller auditing firms in particular should urgently strengthen their risk-based auditing capability. Overall, our findings imply that the mandatory switch to risk-based auditing has optimized audit effort in China.
Keywords: M42; G38; L22; 650; Audit effort; Risk-based audit mode; Corporate governance